Innovation in concrete structures design and construction : proceedings of the international conference held at the University of Dundee, Scotland, UK on 8-10 September 1999 - Dhir, Ravindra K.; Jones, M. Roderick (Thomas Telford, 1999)
Topics discussed in Innovation in Concrete Structures include civil engineering structures, sub-structures, high-rise structures, deep basements, precast concrete construction and housing.